1993
DOI: 10.1029/98jd01224
|View full text |Cite
|
Sign up to set email alerts
|

Factors regulating ozone over the United States and its export to the global atmosphere

Abstract: The factors regulating summertime O3 over the United States and its export to the global atmosphere are examined with a 3‐month simulation using a continental scale, three‐dimensional photochemical model. It is found that reducing NOx emissions by 50% from 1985 levels would decrease rural O3 concentrations over the eastern United States by about 15% under almost all meteorological conditions, while reducing anthropogenic hydrocarbon emissions by 50% would have less than a 4% effect except in the largest urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
143
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 248 publications
(158 citation statements)
references
References 48 publications
12
143
0
Order By: Relevance
“…They tend to be lower than the observed ozone-temperature regression slopes (d [O 3 ]/dT) (Sillman and Samson, 1995). Jacob et al (1993) find in a CTM simulation that this can be explained by the correlation of high temperature with stagnation and sunny skies, not accounted for in simple perturbation studies. Perturbation studies diagnose the partial derivative, while observed correlations diagnose the total derivative.…”
Section: Ozonementioning
confidence: 87%
“…They tend to be lower than the observed ozone-temperature regression slopes (d [O 3 ]/dT) (Sillman and Samson, 1995). Jacob et al (1993) find in a CTM simulation that this can be explained by the correlation of high temperature with stagnation and sunny skies, not accounted for in simple perturbation studies. Perturbation studies diagnose the partial derivative, while observed correlations diagnose the total derivative.…”
Section: Ozonementioning
confidence: 87%
“…A few modeling studies have complimented the field campaigns by examining 3-dimensional distributions of O 3 over the North Atlantic and Europe as a result of North American outflow for extended periods (Kasibhatla et al, 1996;Jacob et al, 1993;Li et al, 2005;Auvray and Bey, 2005). However, uncertainties in emissions profiles, the lack of observations for the initialization of chemical fields, and the inherent uncertainties in the modeling of atmospheric circulations and chemical processes present significant challenges in interpretation of the results (Auvray et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As such, it is crucial to understand the processes that modulate surface ozone concentrations in this region. Temperature is consistently identified as the most important meteorological variable influencing surface ozone concentrations (Aw and Kleeman, 2003;SanchezCcoyollo et al, 2006;Steiner et al, 2008;Dawson et al, 2007), Jacob and Winner (2009) describe how this temperature dependence can be decomposed into components such as stagnation (Jacob et al, 1993;Olszyna et al, 1997)…”
Section: Introductionmentioning
confidence: 99%